Insight Into Nicotinamide Adenine Dinucleotide Homeostasis as a Targetable Metabolic Pathway in Colorectal Cancer - Colombo, Giorgia; Gelardi, Edoardo Luigi Maria; Balestrero, Federica Carolina; Moro, Marianna; Travelli, Cristina; Genazzani, Armando A. (Frontiers in Pharmacology, 2021)
Tumour cells modify their cellular metabolism with the aim to sustain uncontrolled proliferation. Cancer cells necessitate adequate amounts of NAD and NADPH to support several enzymes that are usually overexpressed and/or overactivated. Nicotinamide adenine dinucleotide (NAD) is an essential cofactor and substrate of several NAD-consuming enzymes, such as PARPs and sirtuins, while NADPH is important in the regulation of the redox status in cells. The present review explores the rationale for targeting the key enzymes that maintain the cellular NAD/NADPH pool in colorectal cancer and the enzymes that consume or use NADP(H).